Dissociative Identity Disorder And Its Significance To Nina Sayer's Personality Development - Tiara Wulandari; Samanik Samanik (Faculty of Arts and Education, 2023)
AbstractThe portrayal of mental illness is often depicted in movies through characters’ characterization. As literary work’s purpose focuses on the words and on a conscious and consider arrangement of the words to produce a pleasing or enhancing effect, it can be concluded that movie is one of the best literary work as the tools for portraying the phenomenon of life. This research focuses on the movie entitled Black Swan that was released in 2010. By using that movie, the researcher aims to reveal the psychological issue suffered by the main character, Nina. Through the movie, it is believed that behind the soft and kind attitude of Nina, there was a master of evil and sensual role. Considering that, this research aims to reveal the portrayal of Dissociative Identity Disorder (DID) as seen through Nina in the movie. Furthermore, this research also aims to see the impacts obtained by Nina to her personality development. To conduct the analysis, the researcher used the DID theory by Diagnostic Statistical Manual of Mental Disorder (DSM) as well as the personality theory by Carl Rogers. There are seven symptoms used to reveal the existence of DID in the main character. Meanwhile, there are three components of personality to see the personality development of the main character. To present the data, the researcher used descriptive qualitative methods to describe and explain the issue of DID and personality changing in Nina. Hence, the data are in the form of dialogues and scenes that were taken from the movie. The findings of this research found that Nina Sayer in the movie of Black Swan fulfilled all the symptoms of DID. Due to her DID, Nina also showed the personality changes, by showing her development on her self-worth, self-image, and ideal-self. It happened due to the tense and burden Nina got during her practice time as the Swan Queen. Keywords: Black Swan, dissociative identity disorder, personality.